Pengaruh Inflasi dan Nilai Tukar terhadap Ekspor Produk Halal Indonesia Periode 2016-2020 - Erika Sovia Zahrianti; Wirawan Fadly (Institut Agama Islam Negeri Ponorogo, 2022)
The potential for halal products in the global market is currently experiencing rapid development, marked by an increase in demand every year. However, as the largest Muslim country is still in the spotlight because of the low export of halal products and even far behind non-Muslim countries. It may be influenced by inflation and exchange rate fluctuations in Indonesia. This study uses time-series data for the period January 2016-December 2020 with the Auto-Regressive Distributed Lag Models (ARDL) analysis method. The results show that (1) Inflation has no significant effect on exports of halal products in the short and long term. (2) The exchange rate has a negative and significantly effect on exports of halal products in the short term, but has no significant effect in the long term. (3) Inflation and exchange rates simultaneously have a significant effect on the export of halal products with a contribution of 32.06%.